The Position of Women in the Customary Law Inheritance System in Indonesia - Heryani, Nurmala; Pangalila, Indrati (Legal Frontier, 2025)
This study explores the position of women in Indonesia’s customary law inheritance systems, which vary across ethnic groups and regions. While national legal frameworks have recognized gender equality, customary inheritance practices often reflect patriarchal norms that limit women's rights to inherit property. In some traditions, women are excluded entirely from inheritance, whereas in others they receive limited or conditional rights. This research analyzes how such norms persist despite Indonesia’s legal commitments to equality, examining the cultural, religious, and historical underpinnings of customary law. Through doctrinal and socio-legal analysis, the study evaluates how customary practices align or conflict with national laws, particularly the 1945 Constitution and the Marriage Law. It also considers recent jurisprudence and legal reform efforts aimed at harmonizing customary law with principles of justice and gender equality. The findings reveal a complex interplay between tradition and modern legal standards, emphasizing the need for culturally sensitive yet rights-based legal integration to ensure equitable inheritance rights for women